Identification of One Class of Closed-Loop Nonlinear Dynamic Systems in the Frequency Domain - Shanshiashvili, Besarion; Kavlashvili, Nugzar (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The problems of structure and parameter identification of nonlinear dynamic systems operating with positive feedback in the frequency domain are considered. It is assumed that the input to the investigation system is a harmonic signal. The identification problems are considered on a set of block-oriented models, the elements of which are Hammerstein and Wiener models with unitary feedback. Taking into account the peculiarities of such systems functioning in manufacturing, the equations describing the models are reduced to ordinary nonlinear differential equations, known as the Riccati equation. The developed method for identifying the model structure is based on observations of the system's input and output variables in a steady state. The solution of the parameter identification problem is carried out by the method of least squares. The developed identification method is investigated in terms of accuracy.